Frequency of Retinopathy of Prematurity in Premature Neonates with a Birth Weight below 1500 Grams and a Gestational Age Less than 32 Weeks: A Study from a Tertiary Care Hospital in a Lower-Middle Income Country… - Sohaila, Arjumand (Public Library of Science, 2014)
INTRODUCTION: Retinopathy of prematurity (ROP) is a treatable cause of blindness in neonates. In Pakistan, ROP is often not recognized early because screening and treatment programs are not yet in place in most neonatal units, even in tertiary care hospitals. It is hoped that this report will help inform medical professionals of the magnitude of the problem and help to design appropriate management strategies. OBJECTIVES: The aim was to determine the frequency of ROP in premature and very low birth weight (BW) neonates (BW<1500 g and gestational age (GA) <32 weeks). STUDY DESIGN: Cross-sectional study. STUDY SETTING: Neonatal intensive care unit (NICU) of a tertiary care hospital in Karachi, Pakistan. STUDY DURATION: From June 2009 to May 2010. SUBJECTS AND METHODS: Neonates with a Birth weight (BW) <1500 g and Gestational Age (GA) <32 weeks who were admitted to the NICU and received an eye examination, or were referred for a ROP eye examination as an outpatient, were included in the study. GA was estimated from intrauterine ultrasound findings. Neonates with major congenital malformations, syndromes or congenital cataracts or tumors of the eyes, and those that died before the eye examination or did not attend the out patients department for an eye examination, were excluded. The neonatal eye examination was performed by a trained ophthalmologist at 4 or 6 weeks of age. RESULTS: Out of 86 neonates, ROP was identified in nine neonates (10.5%) at the first eye examination. ROP was significantly associated with BW (P = 0.037), GA (P = 0.033), and chronological age (P<0.001). CONCLUSIONS: we identified ROP in 10.5% of neonates at first eye examination. Significant associations between ROP and a GA<32 weeks and a BW<1500 g were also observed.we also stress that serial follow-up of neonates at risk for ROP is important when making a final diagnosis.